SOX Transcription Factors in Endothelial Differentiation and Endothelial-Mesenchymal Transitions - Yao, Yucheng; Yao, Jiayi; Boström, Kristina I. (Frontiers in Cardiovascular Medicine, 2019)
The SRY (sex determining region Y)-box (SOX) transcription factors were first identified as critical regulators of male sex determination but are now known to play important role in vascular development and disease. SOX7, 17 and 18 are essential in endothelial differentiation and SOX2 have emerged as essential mediator of endothelial-mesenchymal transitions (EndMTs), a mechanism that enables the endothelium to contribute cells with abnormal cell differentiation to vascular disease such as calcific vasculopathy. Here we review the information on the SOX transcription factors in endothelial differentiation and EndMTs contributing to vascular calcification.